Narrativization of Macedonian tradicional dances - Zdravkova-Djeparoska, Sonja (Institute of Ethnology and Folklore Research and ICTM Study Group on Ethnochoreolog, 2015)
This paper aims to show the ways of narrativization where performances of traditional dance in Macedonia are associated with a specific meaning and text. In traditional Macedonian dance we follow two levels of narrativization: one is the performance whose meaning is supplemented with various dramatic elements added, and the second is the long process of creating meaning in some chain dances as a result of historical and processes of national marking. The first level includes several chain dances from the professional ensemble Tanec. The second level of narrativization dance, is exampled by Teshkoto, carrying cult significance for the Macedonians. It gained its meaning gradually as part of the process of creating national symbols.
Keywords: Macedonia, Teshkoto, Komitsko, dramatization, identity